Memajukan Literasi Anak Melalui Strategi Membaca Menyenangkan - Fahrunnisa; Enda Lovita Pandiangan; Tuti Rezeki Awaliyah Siregar (Fusion: Jurnal Pengabdian kepada Masyarakat, 2022)
This service activity is carried out with the aim of implementing and developing a literacy program at the Private Bi Al-Nazhar Madrasah (MI) Jl. development of Hamlet III Pekubuan Kec. Tanjung Pura, Kab. Langkat, North Sumatra. The expected result is that educational institutions are motivated to introduce students by providing and completing a collection of reading materials with various types of interesting themes in the library. Because the library has a very important role not only as a learning center but also as a center for learning and fostering talent and interest in reading, writing for children to have enthusiasm, honing the potential that exists in children and being able to create a warm and effective environment to make literacy activities fun and enjoyable. Creating a conducive and comfortable learning atmosphere for children and teachers are also expected to be able to use information and facilitate media intelligently so that it has a positive impact on the learning process, effectiveness and success in teaching in schools.